Irrigating Africa: policy barriers and opportunities for enhanced productivity of smallholder farmers - Mwamakamba, Sithembile Ndema; Sibanda, Lindiwe Majele; Pittock, Jamie; Stirzaker, Richard; Bjornlund, Henning; Rooyen, Andre F. van; Munguambe, Paiva; Mdemu, Makarius Victor; Kashaigili, Japhet J. (Informa UK Limited, 2017)
African governments have ambitious plans to expand irrigated agriculture, though existing smallholder schemes have largely failed to use land and water sustainably or become profitable. Six government-owned irrigation schemes in Mozambique, Tanzania and Zimbabwe were assessed to identify common policy barriers and opportunities for higher productivity among smallholder farmers. Issues like insecure land tenure systems, unclear institutional arrangements and poor access to markets have contributed to limited profitability. Reform of currently insecure land tenure, strengthening farmer organizations and reforming policies are recommended so that governments step back from scheme management and foster market linkages to enable more profitable irrigated agriculture.